Analysis of the composition of black cumin for the purpose of developing a component-concentrate based on milk whey and synthesised nigelone for use in the cosmetic industry - M. A. Chikatueva; S. A. Yemelyanov (Современная наука и инновации, 2025)
Consumer preference studies conducted in the cosmetics industry consistently show an advantage among components of natural origin. Important criteria in the development of cosmetics are the absence of toxic, allergic reactions, the ability of intracellular delivery of active substances and the provision of prolonged biological action. It seems relevant to our creative team to develop a concentrate component based on a unique composition of whey and an effective actioxidant - nigelog from black cumin, which will meet the modern criteria of innovative cosmetics industry products.